PENERAPAN PERMAINAN DOMINO SEBAGAI UPAYA PENINGKATAN PRESTASI BELAJAR IPA SISWA KELAS VI DI SDN 4 KURANJI KOTA MATARAM - JAFAR ABDULLAH (GANEC SWARA, 2018)
All this time writer do science learning by using group discussion method and assignment. However, based on the analysis of the achievement of competence on students' understanding, especially on the material of plant breeding, students achievement is still low. This is indicated by the low test value on breeding.       The author improves the way of learning to improve student learning achievement about breeding by implementing procedures and the use of learning media that is not boring, in the form of domino cards. The domino game is one of the strategies that can make students happy to learn by applying the principle: "Learning while Playing". Students who are happy in learning gain better understanding and memory. The problem solving used in this classroom action research, is learning using dominoes. With this game students play an active role in learning, so that students experience meaningful learning that is organized in an active, creative, effective, and fun learning (PAKEM).         In the research has been determined the final success indicator of 75% of students (21 students) reached completeness of 62. After the research carried out as much as 2 cycles, student achievement increases. The average of the results of the first cycle test is 52.69, and in the second cycle increases to 76.48, while for the class completeness increased from 60% at the initial condition before the study was conducted to 84% of students achieve mastery. Thus, it can be concluded that "Student learning achievement in Science Lessons in Class VI SDN Kuranji can be improved through Domino Game"